Scoping Review: Hubungan antara Status Perokok Pasif (Secondhand Smoker) dengan Risiko Penyakit Paru Obstruktif Kronik (PPOK) pada Pekerja di Perkantoran - Farhah Zakiah; Annisa Rahmah Furqaani; Susanti Dharmmika (Bandung Conference Series: Medical Science, 2022)
Abstract. Secondhand smoke (SHS) is a term for someone who are exposing to secondhand smoke from an active smoker. Exposure to cigarette smoke itself has been proven to be a risk factor for various health problems and is also a serious problem in the workplace. As a result of smoking and exposure to cigarette smoke, it increases the risk of several diseases, such as chronic obstructive pulmonary disease (COPD) which is included in the type of non-communicable disease and is a disease that is a health problem in the world. The purpose of this study was to determine the relationship between secondhand smoke status and the risk of chronic obstructive pulmonary disease in office workers. The study used the scoping review method which was carried out by analyzing articles published in 2016-2021 on three databases, namely Science Direct, Pubmed and Google Scholar, which matched the inclusion criteria of 8,600 articles. There are 5 articles that meet the inclusion criteria. After adjustments were made to the exclusion criteria and the feasibility test using the Joanna Briggs Institute's critical appraisal checklist and based on PICOS, 5 articles were obtained. In one article, there is a comparison between smokers and non-smokers, 196 (63.84%) were exposed to passive smoke (non-smokers), and 24 (12.24%) had COPD. Another article states that the prevalence of COPD is 2.2% (2.4 million) in those who have never smoked. The conclusion of this study shows that there is a relationship between passive smoking and the risk of COPD in the workplace, one of them in the office area. Abstrak. Perokok pasif atau secondhand smoke (SHS) merupakan istilah bagi seseorang yang terpapar asap rokok dari seorang perokok aktif. Paparan asap rokok sendiri telah terbukti sebagai faktor risiko berbagai masalah kesehatan dan juga menjadi permasalahan serius di tempat kerja. Akibat merokok dan paparan asap rokok, adalah meningkatkan risiko beberapa penyakit, seperti penyakit paru obstruktif kronik (PPOK) yang termasuk kedalam jenis penyakit tidak menular dan merupakan penyakit yang menjadi masalah kesehatan didunia. Tujuan penelitian ini adalah untuk mengetahui hubungan antara status perokok pasif (secondhand smoke) dengan risiko kejadian penyakit paru obstruktif kronik pada pekerja di perkantoran. Penelitian menggunakan metode scoping review yang dilakukan dengan cara menganalisis artikel yang dipublikasikan pada tahun 2016-2021 pada tiga database yaitu Science Direct, Pubmed dan Google Scholar yang sesuai dengan kriteria inklusi sebanyak 8.600 artikel. Artikel yang sesuai dengan kriteria inklusi berjumlah 5 artikel. Setelah dilakukan penyesuaian dengan kriteria eksklusi dan uji kelayakan menggunakan Joanna briggs Institute critical appraisal checklist dan berdasarkan PICOS didapatkan 5 artikel. Pada salah satu artikel terdapat perbandingan antara pekerja perokok dan bukan perokok didapatkan sebanyak 196 (63,84%) yang terpapar asap pasif (non-perokok), dan 24 (12,24%) di antaranya menderita PPOK. Artikel lain menyebutkan bahwa prevalensi PPOK 2,2% (2,4 juta) pada mereka yang tidak pernah merokok. Kesimpulan pada penelitian ini menunjukkan bahwa terdapat hubungan antara perokok pasif dengan risiko kejadian PPOK di tempat kerja salah satunya di area perkantoran.